Unusual Constellation of Anomalies in Maternal Diabetes Syndrome: Bifurcated Distal Phalanx of the Thumb, Cleft Lip, and Patent Ductus Ateriosus - IA Rad; AR Afshar (Tehran University of Medical Sciences, 2008)
Maternal hyperglycemia during early gestation is associated with an increased incidence of congenital anomalies. A case of maternal diabetes syndrome is presented here with a rare constellation of congenital anomalies, i.e., bifurcated distal phalanx of the thumb, patent ductus arteriosus and cleft lip.